2017
DOI: 10.1037/dev0000381
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in infants’ categorization of anger and disgust facial expressions.

Abstract: For decades, scholars have examined how children first recognize emotional facial expressions. This research has found that infants younger than 10-months can discriminate negative, within-valence facial expressions in looking time tasks, while children older than 24-months struggle to categorize these expressions in labeling and free-sort tasks. Specifically, these older children, and even adults, consistently misidentify disgust expressions as anger. While some scholars have hypothesized that young infants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 44 publications
(101 reference statements)
5
42
1
Order By: Relevance
“…As noted earlier, Ruba et al. () reported that 10‐month‐olds categorize the anger/disgust contrast in faces. However, Ruba et al.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…As noted earlier, Ruba et al. () reported that 10‐month‐olds categorize the anger/disgust contrast in faces. However, Ruba et al.…”
Section: Discussionmentioning
confidence: 61%
“…It is possible that 5‐month‐olds’ failure to exhibit categorical perception of anger/disgust contrasts in Experiments 1 and 2 is because these emotions are not fully differentiated by 5 months, and it takes longer for the categorical boundary between anger and disgust to develop (Ruba et al., ). One reason for this might be the overlap in several physical facial features (e.g., face muscular structure) associated with angry and disgusted expressions (Aviezer, Hassin, Bentin, & Trope, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a handful of studies have used negative facial expressions during both habituation and test. These studies indicate that 4- to 18-month-olds can form a category of anger (i.e., after habituation to anger expressions) and differentiate this category from novel sad, fear, and disgust expressions (Ruba, Johnson, Harris, & Wilbourn, 2017; Schwartz et al, 1985; Serrano et al, 1992). Moreover, 10- and 18-month-olds can form a category of disgust and differentiate this category from anger expressions at test (Ruba et al, 2017).…”
Section: Categorization Of Emotional Expressionsmentioning
confidence: 81%
“…Finally, most studies assume that concepts are perceptual distillates. Categories would result from comparing and abstracting physical properties of objects (e.g., Bomba & Siqueland 1983;Casasola & Ahn 2018;Quinn & Johnson 2000;Ruba et al, 2017;Stavans & Baillargeon 2018;Younger & Fearing 1999, 2000. However, this prospect raises hard problems at the epistemological level (for an in-depth discussion, see Alessandroni, 2020;Alessandroni & Rodríguez, in press).…”
Section: Discussion: Methodological Limitationsmentioning
confidence: 99%